ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI RISIKO INVESTASI SAHAM PADA PERUSAHAAN TELEKOMUNIKASI - Yanti, Ni Putu Ayu Dewi; Rasmini, Ni Ketut (E-Jurnal Akuntansi, 2014)
This study aims to determine the influence of the deposit interest rate, exchange rate, capital structure, operating leverage and liquidity of the company at the risk of investments in telecommunications companies that went public in the Indonesia Stock Exchange. The research sample was determined by census method as many as six telecom company registered in the PT. Indonesia Stock Exchange from 2008 until 2012. Analysis using multiple linear regression analysis. Conclusion The results of the study are: operating leverage and liquidity of the company and a significant positive effect on the risk of investing in stocks, while the deposit interest rate, exchange rate and capital structure and insignificant negative effect on the risk of stock investment.
Keywords: factor macro, micro, investment risk